Small-scale area effect on species richness and nesting occupancy of cavity-nesting bees and wasps - Loyola,Rafael D. (2011)
Small-scale area effect on species richness and nesting occupancy of cavity-nesting bees and wasps. The research was conducted in an urban forest remnant in southeast Brazil. We tested the predictions of the following hypotheses: (1) larger areas present higher species richness of bees and wasps, (2) solitary bees and wasps occupy more nests in larger areas, (3) rare species occupy more nests in smaller areas. We sampled Aculeate bees and wasps using trap nests from February to November 2004. We placed trap nests in sampling units (SU) with different size (25, 100 and 400 m²) located in 6 ha of secondary mesophytic forest. One hundred and thirty-seven trap nests were occupied by seven species of bees and four species of wasps. We found an increase in wasp, but not bee species richness following increase in SU size. Hymenoptera richness (i.e. bees plus wasps) was also greater in larger SU. Both the number and density of occupied nests increased with SU size. The wasp Trypoxylon lactitarse responded significantly to area size, larger SU having more occupied nests. The same pattern was exhibited by the wasp Auplopus militaris, the Megachile bee species, and the bee Anthodioctes megachiloides. Only Trypoxylon sp. was not affected by SU size. Our results show that cavity-nesting bee and wasps respond differently to the area effects. Such findings must be complemented by information on the frequency and dynamics of area colonization and nest occupancy by species of solitary Hymenoptera.